Impact of electronic fiscal devices of value added tax collection process: The case of Tanzania Revenue Authority-Tanga city. - Salim, S. Bakar (Mzumbe University, 2024)
A dissertation submitted to School of Business Administration as a partial fulfilment of the requirements for award of the Master Degree of Business Administration (MBA-CM) of Mzumbe University